2002
DOI: 10.1128/jb.184.12.3416-3418.2002
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for NusG for Transcription Antitermination In Vivo by the λ N Protein

Abstract: Transcription antitermination by the bacteriophage N protein is stimulated in vitro by the Escherichia coli NusG protein. Earlier work suggested that NusG was not required for N activity in vivo. Here we present evidence that NusG also stimulates N-mediated transcription antitermination in intact cells. (8,20), is an abundant transcription elongation factor that modulates Rho-dependent transcription termination (22,24,25). Rhodependent termination is inhibited by depletion or overexpression of NusG (2, 24). Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…The NusA and NusD/Rho functions were previously suspected to be essential for bacterial growth, since conditional lethal mutants of these genes had been isolated (13,17,39,56). A nusG knockout was shown to be nonviable (72), while a nusA knockout could be obtained only in the presence of attenuating rho mutations (71). At the same time, rho (45) and nusG (27) been reported as viable.…”
Section: Discussionmentioning
confidence: 99%
“…The NusA and NusD/Rho functions were previously suspected to be essential for bacterial growth, since conditional lethal mutants of these genes had been isolated (13,17,39,56). A nusG knockout was shown to be nonviable (72), while a nusA knockout could be obtained only in the presence of attenuating rho mutations (71). At the same time, rho (45) and nusG (27) been reported as viable.…”
Section: Discussionmentioning
confidence: 99%
“…22,41,42 The recessive nusG-G146D mutation is the first example of a viable nusG allele that confers a transcription termination-defective phenotype. The mutation phenocopies a defective rho allele (rho-A243E) in conferring phage P2 resistance and relief of transcriptional polarity at each of four widely separated genetic loci (Figure 1), implying a global deficiency of Rho-dependent transcription termination in the nusG mutant.…”
Section: Discussion Nusg Role In Global Rho-dependent Transcription Tmentioning
confidence: 99%
“…These investigators suggested that the very rapid transcription of rRNA by T7 RNA polymerase uncouples the delicate relationship between transcription and ribosomal assembly (18). This result raises the possibility that the twofold antiterminator-dependent increase in the transcription elongation rate is necessary for the proper folding of the rRNA and the subsequent assembly of the ribosomal subunits (38,40). c cat/bla mRNA ratio normalized to that for pSL102.…”
Section: Discussionmentioning
confidence: 99%